The role of plasma C-reactive protein in the evaluation of antibiotic treatment in suspected neonatal sepsis (Faculty of Medicine Universitas Indonesia, 2001)
Analysis of serial C-reactive protein (CRP) levels was done to evaluate the effectiveness of antibiotic treatment in 35 suspected neonatal sepsis (SNS) patients who were hospitalized at Cipto Mangunkusumo Hospital, Jakarta. This cross sectional study was conducted from April to September 1999. Among 35 SNS patients, 18 had positive blood culture, 10 of which had positive CRP level at the time of diagnosis. Among 17 patients with negative blood culture, 9 had negative CRP level. Serial CRP in severe cases with positive CRP titer showed persistent high CRP level, and in those with negative CRP titer rose up to day 4 of treatment. On the other hand patients who were discharged and have negative blood culture demonstated low CRP level in day 4. This study confirms the benefit of serial CRP examination in the evaluation of antibiotic treatment in SNS. (Med J Indones 2001; 10:16-21) Keywords: neonatal sepsis, antibiotic treatment, serial CRP level measurements, prognosis